Process of Floor Formation in Rice Fields Using A Disc Floor Collector and Its Mechanization Technology - A. N. Khudoyarov; D. Khudoynazarov; Yo. Mukimova (American Journal of Botany and Bioengineering, 2026)
This article provides a detailed description of the essence of floor formation in rice fields using a disc floor collector, its effects on rice growth and productivity, as well as the traditional and mechanized methods of implementing the process. In particular, the stages of floor formation — soil loosening, chiseling, leveling, and flooding — and the machinery used at each stage are analyzed. Research results show that in fields where quality floor formation is achieved with a disc floor collector, water consumption decreases by 18-25%, fertilizer efficiency increases by 12-18%, and final yield increases by 6-10 centners per hectare.